Tradisi Ziarah di Banten - Jessika Jessika; Siti Sarah; Ahmad Maftuh Sujana (Reflection : Islamic Education Journal, 2025)
The tradition of pilgrimage in Banten is one of the cultural and religious heritages that still lives today. Pilgrimages to the graves of prominent saints and scholars, such as Sultan Maulana Hasanuddin and Sheikh Nawawi Al-Bantani, are spiritual activities undertaken by the community, both from the local area and outside the region. This tradition not only serves as a tribute to religious figures, but also as a means to get closer to God while strengthening social bonds among pilgrims. In addition to the religious aspect, this pilgrimage activity also has a significant economic impact on the surrounding community, especially in the trade and service sector. This article will discuss the history, meaning, and dynamics of the pilgrimage tradition in Banten in the cultural and social context of the community.